2009
DOI: 10.1111/j.1475-6773.2008.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Medicaid Undercount in the Current Population Survey: Preliminary Results from Record Linking

Abstract: Objective. To assess reasons why survey estimates of Medicaid enrollment are 43 percent lower than raw Medicaid program enrollment counts (i.e., “Medicaid undercount”). Data Sources. Linked 2000–2002 Medicaid Statistical Information System (MSIS) and the 2001–2002 Current Population Survey (CPS). Data Collection Methods. Centers for Medicare and Medicaid Services provided the Census Bureau with its MSIS file. The Census Bureau linked the MSIS to the CPS data within its secure data analysis facilities. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 12 publications
0
51
0
Order By: Relevance
“…Specifically, we link individual-level CPS data to corresponding individual-level administrative data from the Centers for Medicare & Medicaid Services' (CMS) Medicaid Statistical Information System (MSIS). Earlier studies have shown that CPS Medicaid reporting has a substantial number of errors associated with it (Davern, Baugh, Call, Cox, & Klerman, 2009;Klerman, Davern, Call, Lynch, & Ringel, 2009). In this paper, we examine CHIP reporting in the CPS and we show that CPS CHIP reporting is far less accurate than Medicaid reporting, calling into question the value of the CHIP responses in the CPS for researching the CHIP program.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Specifically, we link individual-level CPS data to corresponding individual-level administrative data from the Centers for Medicare & Medicaid Services' (CMS) Medicaid Statistical Information System (MSIS). Earlier studies have shown that CPS Medicaid reporting has a substantial number of errors associated with it (Davern, Baugh, Call, Cox, & Klerman, 2009;Klerman, Davern, Call, Lynch, & Ringel, 2009). In this paper, we examine CHIP reporting in the CPS and we show that CPS CHIP reporting is far less accurate than Medicaid reporting, calling into question the value of the CHIP responses in the CPS for researching the CHIP program.…”
Section: Introductionmentioning
confidence: 84%
“…The CPS Annual Social and Economic supplement is fielded annually and is not a longitudinal dataset, so MSIS data could simply be matched with the CPS and appended together. The U.S. Census Bureau (2007Bureau ( , 2008 and Davern et al (2009) In brief, CMS provided the Census Bureau with extracts of its MSIS file containing state monthly individual-level data on Medicaid coverage. In its secure data facility and with appropriate protections of privacy, confidentiality, and data security, the Census Bureau matched all individual-level data from the MSIS file to the corresponding CPS records.…”
Section: The Linked Datamentioning
confidence: 99%
“…We refer to Medicaid and CHIP together as Medicaid through the remainder of this article.We chose to combine the programs because this is how the data are typically reported and because previous studies of Current Population Survey data have suggested that CHIP enrollees might incorrectly indicate in the survey that Medicaid was their primary source of health insurance coverage. 7 The proportion of children living in poverty is related to but distinct from state-level per capita income used to set the federal match rates. The Current Population Survey was also the source of data regarding elderly people enrolled in Medicaid in each state during the study period.…”
Section: Study Data and Methodsmentioning
confidence: 99%
“…Studies comparing self-reported Medicaid status in the CPS with administrative counts find that respondents in the CPS underreport participation in Medicaid, which artificially inflates the number of uninsured (9); however, misreporting occurs in all directions, and some Medicaid enrollees report that they are privately insured, whereas some nonenrollees report Medicaid coverage (35).…”
Section: Behavioralmentioning
confidence: 99%